9-Demethoxy-medicarpin: A potential bone health supplement for the management of protein deficiency-induced bone loss in growing rats. (15th January 2023) - Singh, Krishna Bhan; Awasthi, Pallavi; Srivastava, Kamini; Rawat, Kundan Singh; Rai, Reena; Parveen, Sajiya; Gautam, Abnish K.; Vats, Ravi P.; Goel, Atul; Singh, Divya
Graphical abstract: Highlights: 9-Demethoxy-medicarpin (DMM) improved BMD in protein deficiency induced bone loss. DMM treatment led to increase in serum albumin which is vital for the body growth. DMM supplementation led to high ALP levels, which are important during growth spurts. DMM can be used as potential bone health supplement. Abstract: Human skeleton requires an adequate supply of many different nutritional factors for optimal growth and development. The role of nutrition in bone growth has piqued interest in recent years, especially in relation to maximizing peak bone mass and reducing the risk of osteoporosis. Protein deficiency-induced bone loss was induced in female growing rats. All experimental rodent diets were prepared as per recommendations for growing animals. 9-Demethoxy-medicarpin (DMM) treatment was given to growing Sprague Dawley (SD) rats at 1 mg and 10 mg dose orally for 30 days. Bones were collected for bone mineral density (BMD). Bone marrow cells were isolated from femur for calcium nodule formation. Serum samples were collected for biochemical parameters. We found that DMM treatment speeds up the recovery of musculoskeletal weakness by replenishing nutrients in proven rodent model. DMM supplementation for four weeks showed significantly increased vertebral, femur and tibial BMD compared with the untreated PD group. Albumin levels were significantly enhanced in treatment groups, in which 10 mg dose imparted a better effect. We conclude that DMM treatment led to increased BMD and biochemical parameters in protein deficient condition in growing rats and has potential as a bone growth supplement.